Developing an Original Argument: A Strategy for College Writing. Issue 3 (2nd July 2016) - Medvedeva, Maria; Recuber, Timothy
ABSTRACT: An essay's motive or research problem consists of the rhetorical moves illuminating why that essay matters—what puzzling elements of a primary source it resolves, which contradictions in the data it explains, or what gaps in the literature it fills. This article invites college instructors to dedicate some of their classroom time to teaching students how to construct original, motive-driven arguments. More specifically, the article describes the conceptual triangle technique that uses a simple three-point concept map as the first step in active argument building. This technique is simple and flexible enough to be adapted across subject areas, data, and disciplines. The focus on scholarly motive in general and the use of the conceptual triangle in particular can be effective ways to help academic writers at all levels to develop original arguments that matter.